2009
DOI: 10.1108/02635570911002243
|View full text |Cite
|
Sign up to set email alerts
|

Customer knowledge management in the natural cosmetics industry

Abstract: PurposeThis paper aims to examine the level of customer knowledge (CK) for natural cosmetic products, namely Bulgarian rose products, in three European countries – Bulgaria, Montenegro and Italy – and to propose appropriate solutions for its management.Design/methodology/approachThe research structure is based on a questionnaire and represents a part of the general investigation about the nature of the Bulgarian rose products. The study includes the responses to priority questions on customers' knowledge about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 6 publications
1
37
0
5
Order By: Relevance
“…Ma and Yang (2018) found that Chinese females purchase cosmetic products relying on quality, price, and delivery. Dealing with the cognitive components of attitudes, Dimitrova et al (2009) indicated that consumers' cognition could be learnt and changed through product marketing. To summarise, consumer attitudes vary from person to person due to internal factors like different psychological and emotional feelings and external factors like family preference and social and cultural status.…”
Section: Factors Influencing the Formation Of Attitudementioning
confidence: 99%
“…Ma and Yang (2018) found that Chinese females purchase cosmetic products relying on quality, price, and delivery. Dealing with the cognitive components of attitudes, Dimitrova et al (2009) indicated that consumers' cognition could be learnt and changed through product marketing. To summarise, consumer attitudes vary from person to person due to internal factors like different psychological and emotional feelings and external factors like family preference and social and cultural status.…”
Section: Factors Influencing the Formation Of Attitudementioning
confidence: 99%
“…According to the euromonitor data report released in 2008, the world cosmetics market growth increased from 170 billion Euros in 2001 to more than 220 billion Euros in 2007. Moreover, this market is expected to grow at an average of 3% per annum and in 2011 will reach 250 billion Euros 1. Thus, safety and quality control of cosmetic products is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, organizations' focus should be on general competencies of customers such as product development culture and rational coordination with the organizations (Lopez‐Nicolas & Molina‐Castillo, ). Such a marketing method is called “external knowledge absorption” (Dimitrova et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%